Pengaruh Promosi dan Store Exterior Terhadap Minat Beli Konsumen Pada Bisnis Retail Minimarket - Andayani Andayani; Ronda Deli Sianturi (Journal of Business and Economics Research (JBE), 2021)
Facing intense competition in business, a strategy is needed to encourage consumers to make purchases. With the presence of more and more mini markets in Indonesia competing in serving consumer needs and greatly assisting the government in reducing the number of unemployed, the availability of these mini markets is highly desired by both rural and urban communities. This study aims to determine how the effect of promotion and store exterior on people's buying interest. The results show that the role of minimarkets on people's buying interest is very supportive, because the provision of products that are tailored to the needs of the community is accompanied by a good atmosphere and presentation and service to consumers, so that customers feel satisfied and decide to buy. Thus, the convenience of shopping at an affordable price and an integrated and creatively designed building leads consumers to decide to buy the products they need